Impact and Predictive Value of Prostate Weight on the Outcomes of Nerve Sparing Laparoscopic Radical Prostatectomy in Patients with Low Risk Prostate Cancer - Jiang, Dong-Gen; Xiao, Chu-Tian; Mao, Yun-Hua; Qiu, Jian-Guang; Si-tu, Jie; Lu, Min-Hua; Gao, Xin (Urology Journal, 2019)
Purpose: To investigate the impact of prostate weight on outcomes of nerve sparing laparoscopic radical prostatectomy (LRP) and assess its predictive value on postoperative continence and potency recovery. Materials and Methods: We conducted a retrospective study on the clinical data of 165 patients with low risk prostate cancer (PCa) who underwent nerve sparing LRP. All the patients included had normal preoperative urinary and sexual function. The association of prostate weight with perioperative data was assessed using Spearman correlation coefficient. Univariate and multivariate Cox regression analyses were employed to identify prognostic predictors for continence and potency recovery. Results: Increased prostate weight was significantly associated with older age, higher prostate-specific antigen (PSA), lower biopsy and pathological T stage and Gleason score, longer operative time, and higher estimated blood loss (P < .05). The continence rates at the 3rd, 6th, and 12th month after surgery were 63.6% (105/165), 87.9% (145/165), and 95.8% (158/165); and the potency rates were 44.8% (74/165), 62.4% (103/165) and 77.6% (128/165), respectively. Furthermore, multivariate Cox analysis showed that patient age (HR = 0.52, 95% CI: 0.35- 0.76) and prostate weight (HR = 0.54, 95% CI: 0.34-0.86) were independent predictors for continence recovery, while only patient age (HR = 0.66, 95% CI: 0.45-0.96) could independently predict potency recovery. Conclusion: Larger prostate size was correlated with older age, higher PSA, lower tumor stage and grade, longer operative time, and more intraoperative blood loss in low risk PCa patients. Increased prostate weight may independently predict poor continence recovery after nerve sparing LRP.